2000
DOI: 10.1163/156853800507444
|View full text |Cite
|
Sign up to set email alerts
|

Variation in age and size among breeding populations at different altitudes in the Japanese newts, Cynops pyrrhogaster

Abstract: The age distribution of Cynops pyrrhogaster was studied by skeletochronology on 12 breeding populations inhabiting altitudes ranging from 120 m to 1140 m on Shikoku Island, Japan. In populations inhabiting altitudes 500 m or less, the mean SVL were smaller than in those that lived at higher altitudes. In populations inhabiting altitudes less than 500 m, minimum age at maturation was three years. In populations inhabiting altitudes of 500 m or more, the minimum age at maturation was four to seven years. The num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 22 publications
0
4
0
2
Order By: Relevance
“…All C. ensicauda except CeM, reared since 1988, died by 2015. CpF was an adult size when purchased in 1987 and thus was considered to be at least two years old (Marunouchi et al, 2000). It survived 35 years until the escape, making it at least 37 years old.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All C. ensicauda except CeM, reared since 1988, died by 2015. CpF was an adult size when purchased in 1987 and thus was considered to be at least two years old (Marunouchi et al, 2000). It survived 35 years until the escape, making it at least 37 years old.…”
Section: Resultsmentioning
confidence: 99%
“…The longevity of C. pyrrhogaster in captive conditions has been reported to be 25 to 50 years old (Sato, 1943; Eguchi et al, 2011; Köhler et al, 2023). The longevity of the wild individuals has been reported to be 23 years as estimated by skeletochronology (Marunouchi et al, 2000) and 31 and 23 years old for males and females, respectively, based on the mark and recapture study (Kusano, 2020). In this study, we confirmed that a female C. pyrrhogaster survived for at least 37 years and that a male C. e. popei did for more than 36 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While age records of 20-25 years are not exceptional for Cynops pyrrhogaster (Sparreboom, 2014) and even historical literature reports refer to 25 years under human care for the species (Wolterstorff, 1928; Senning, 1940), there are only few documented cases of Fire-bellied Newts exceeding an individual age of 40 years (Bogaerts, 2013). Skeletochronological studies estimated the maximum age of wild-caught female C. pyrrhogaster to be 16 years (Marunochi et al ., 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Yüksek rakımlı bölgelerde ve kuzey enlemlerde yaşayan bireyler alçak rakımlı bölgelerde ve güney enlemlerde yaşayanlara göre daha uzun yaşarlar (Smirina, 1994). Genel olarak, ergenliğe ulaşma yaşı ve yaşam süresi, yüksek rakımlarda yaşayan popülasyonlarda, alçak rakımlarda yaşayanlara göre daha fazla olma eğilimindedir ve yapılan birçok çalışmada bu eğilim gösterilmiştir (Caetano et al, 1985;Marunouchi et al, 2000;Maletzky et al, 2004;Kutrup et al, 2005;Altunışık et al, 2014). Düşük sıcaklık dereceleri amfibilerin larval ve juvenil dönemlerindeki büyümelerini ve bunun sonucu olarak ergenliğe ulaşma zamanını etkilemektedir (Altunışık et al, 2014).…”
Section: Veri Analiziunclassified